2013
DOI: 10.1111/bph.12118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key residues involved in adrenomedullin binding to the AM1 receptor

Abstract: We determined the AM22-52 binding epitope for the AM1 receptor extracellular domain using biophysical techniques, heteronuclear magnetic resonance spectroscopy and alanine scanning. KEY RESULTSChemical shift perturbation experiments located the main binding epitope for AM22-52 at the AM1 receptor to the C-terminal 8 amino acids. Isothermal titration calorimetry of AM22-52 alanine-substituted peptides indicated that Y52, G51 and I47 are essential for AM1 receptor binding and that K46 and P49 and R44 have a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 44 publications
1
50
3
Order By: Relevance
“…Our DsbC-assisted disulfide shuffling methodology is distinct from the traditional denaturant-based refolding protocols employed by other groups to produce CLR-RAMP ECD complexes. 17,27,37 We previously employed our methodology to produce several other class B GPCR ECDs with 3 disulfide bonds. [30][31][32][33][34] Here, the methodology was successful for proteins with up to 6 disulfide bonds, which suggests that it may be more broadly applicable to various disulfide bond-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our DsbC-assisted disulfide shuffling methodology is distinct from the traditional denaturant-based refolding protocols employed by other groups to produce CLR-RAMP ECD complexes. 17,27,37 We previously employed our methodology to produce several other class B GPCR ECDs with 3 disulfide bonds. [30][31][32][33][34] Here, the methodology was successful for proteins with up to 6 disulfide bonds, which suggests that it may be more broadly applicable to various disulfide bond-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…22,26,36,37 It was recently demonstrated that the C-terminal eight amino acids of AM, in the context of the 22-52 fragment, constituted the primary AM receptor ECD binding epitope. 27 We examined the ability of N-terminally truncated CGRP and AM peptides of varying lengths to bind their respective tethered receptor ECD fusion proteins in the competition AlphaScreen assay. In agreement with previous studies, we observed that CGRP peptides as short as (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) retained the ability to bind the tethered CGRP receptor ECD fusion protein and that the affinity of the (27-37) fragment was only slightly reduced compared to the (8-37) fragment (Table I).…”
Section: Alphascreen Luminescent Proximity Assay Characterization Of mentioning
confidence: 99%
See 3 more Smart Citations